Impak perlaksanaan amalan persekitaran berkualiti 5S di Institut Teknikal Jepun Malaysia - Mohamed Yusof, Mohd Raris (2013)
SS is the acronym of five Japanese words which Seiri, Seiton, Seisou, Seiketsu and Shitsuke deviate meaning, sort, set in order, sweep, standardize and sustain. This study aims to analyze the efficiency of access to documents and equipments among staffs and students, analyze the effectiveness of working space saving among staffs and the factors that contribute to the success and failure of the implementation of SS in JMTI after certification is received. The study looked at the relevant Departments and Divisions in JMTI involving staffs and students who are involved directly with a minimum data of 1 S people in the last three months of observation starting from January to March 2013. Percentage of document access efficiency is 69 .3 7% better compared to the time before certification, and 44. 66% better with the MPC standard access time. Percentage of equipment access efficiency is 76.S8% better compared to the time before certification and 77. 71 % better compared to the standards in MPC access time. Based on the results from the use of personalized stationery space and the use of staff work space, it was found that the percentage of effectiveness of individual stationery space usage is low which only 4. S% and the percentage of the overall effectiveness of the use of individual workspaces is only 1.49%. The main factors contributing to the success and failure of SS practice are Management, Environment, Personal and Financial. The results from this study on the impact of the SS implementation can help to improve productivity of the work, can be used by JMTI staff and students specially and also for JTM generally.